Geronimo Stilton. #20 and #21 [compact disc, unabridged] - Lobley, Bill (Scholastic, 2010)
Geronimo Stilton, which was originally written in Italian, is a tale about a talking mouse that lives in New Mouse City on Mouse Island, where he works as a journalist for The Rodent's Gazette.